História do Colégio Regina Coeli : de escola confessional à escola comunitária : (Veranópolis/RS, 1948-1980) - Matiello, Marina (My University, 2014)
The present study aimed to tell the history of Regina Coeli School, in the years 1948 to 1980, located in Veranopolis, seeking to analyze the motivations and possible changes resulting from the transition of a confessional school for a community school, noting the school cultures. The choice of time frame is related to important facts, which marked the year 1948 for the beginning of the study, it was this year that the school was renamed to Regina Coeli, with the inauguration of the building built specifically for school. The date of 1980 was determined taking into account data about the school board, which after changing the condition of catholic confessional to community in 1969, kept being administrated by the Sisters of São José by the year 1976. From 1977, it began to be directed by lays, having two directors until 1980. Considering this delimitation, for the construction of the narrative, it was analyzed the school cultures, regarding the spaces, the subjects and school knowledge. Guided the theoretical principles of Cultural History, it was used as methodology the documental analysis, referring to Regina Coeli School, and oral history through interviews with people who participated in the educational institution object of this research. The documents relate to the meeting minutes, the "Verify Report for effect of concession of „preliminary inspection' Gym Regina Coeli", photographs, registration books and newspapers. Interviews were conducted with two former principals, two Sisters of São José (a former teacher and a former student) and two former students, who also acted as teachers in school. The narrative is organized into five chapters, starting with the initial considerations, which details the research process, presenting the objectives and methodology adopted for the study. Then, it presents a brief historical and educational background of Veranópolis, pointing aspects of social, political, cultural, economic and educational development. Following are narrated aspects of school culture of Regina Coeli School, referring to the subjects, spaces and knowledges, in the period in which the school, with the status of Catholic confessional, was administered by the Sisters of São José, covering the period 1948-1969 but also citing aspects of the previous period, from 1917 to 1947, when the school was called São José. Then, discuss the motivations and the transition process of the statute of the school, from Catholic confessional to community, as well as aspects of school cultures in relation to the subjects, spaces and school knowledge of the period 1969-1980. To conclude, the final considerations are exposed, allowing understand that changes in school cultures Regina Coeli School, arising from the transition of statute of Catholic Confessional school for Community School were gradual, as the Sisters continued in Regina Coeli College until 2000, at which time there was a higher tensions. Based on these results and the narrative constructed, highlights the importance of this research to the Veranense community and to the studies in the field of history of education.
O presente estudo teve o propósito de narrar a história do Colégio Regina Coeli, nos anos de 1948 a 1980, localizado em Veranópolis, buscando analisar as motivações e possíveis transformações decorrentes da passagem de uma escola confessional para uma comunitária, atentando para as culturas escolares. A escolha do recorte temporal está relacionada a fatos importantes, sendo demarcado o ano de 1948 para o início do estudo, pois foi neste ano que a escola passou a denominar-se Regina Coeli, com a inauguração do prédio construído especificamente para o colégio. A data limite de 1980 foi determinada levando-se em consideração dados sobre a direção da escola, que depois de ter passado da condição de confessional católica para comunitária, em 1969, continuou sendo administrada por Irmãs de São José até o ano de 1976. A partir de 1977, passou a ser dirigida por leigos, tendo tido dois diretores até 1980. Considerando essa delimitação, para a construção da narrativa, analisaram-se as culturas escolares, no que diz respeito aos espaços, aos sujeitos e aos saberes escolares. Pautada nos pressupostos teóricos da História Cultural, utilizou-se como metodologia a análise de documentos, referentes ao Colégio Regina Coeli, e a história oral, através de entrevistas com sujeitos que participaram da instituição de ensino objeto dessa pesquisa. Os documentos dizem respeito às atas de reuniões, ao “Relatório da verificação para efeito da concessão de „inspeção preliminar‟ Ginásio Regina Coeli”, às fotografias, aos livros de matrículas e aos jornais. As entrevistas foram realizadas com dois ex-diretores, duas Irmãs de São José (uma ex-professora e uma ex-aluna) e duas ex-alunas, que atuaram também como professoras na escola. A narrativa foi organizada em cinco capítulos, iniciando com as considerações iniciais, onde se detalha o processo de pesquisa, apresentando os objetivos e a metodologia adotada para a realização do estudo. Em seguida, apresenta-se um breve contexto histórico e educacional de Veranópolis, apontando aspectos do desenvolvimento social, político, cultural, econômico e educacional. Na sequência são narrados aspectos da cultura escolar do Colégio Regina Coeli, referente aos sujeitos, espaços e saberes, no período em que a escola, com o estatuto de confessional católica, era administrada pelas Irmãs de São José, compreendendo o período de 1948 a 1969, mas citando também aspectos do período anterior, de 1917 a 1947, em que a escola denominava-se São José. Depois, abordam-se as motivações e o processo de transição de estatuto da escola, de confessional católico para comunitário, bem como aspectos das culturas escolares em relação aos sujeitos, espaços e saberes escolares do período de 1969 a 1980. Para concluir, são expostas as considerações finais, que permitem compreendem que as transformações nas culturas escolares do Colégio Regina Coeli, decorrentes da transição de estatuto de escola confessional católica para comunitária, foram graduais, pois as Irmãs continuaram no Colégio Regina Coeli até o ano 2000, momento em que foram observados maiores tensionamentos. Diante dos resultados obtidos e da narrativa construída, evidencia-se a importância dessa pesquisa para a comunidade veranense e para os estudos na área da história da educação.
Keywords: Colégio Regina Coeli - História; Escolas comunitárias; Escolas - História - Veranópolis (RS); Confessional catholic school; Community schools; History of Institutions School